2003
DOI: 10.1182/blood-2002-08-2464
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of BCL3 differentiates t(2;5)(p23;q35)-positive anaplastic large cell lymphoma from Hodgkin disease

Abstract: Anaplastic large cell lymphoma (ALCL) with t(2;5)(p23;q35) and Hodgkin disease (HD) share many cellular features, including expression of CD30. We compared gene expression profiles of 4 ALCL (Karpas 299, SU-DHL-1, DEL, SR-786) and 3 HD cell lines and found that BCL3, which encodes a nuclear protein belonging to the IB family of inhibitors of nuclear factor-B (NF-B) transcriptional factors, was expressed at higher levels in ALCL than HD. Northern and Western blotting analyses confirmed the high-level expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 47 publications
6
43
1
Order By: Relevance
“…High BCL3 expression has also been reported in a subgroup of anaplastic large-cell lymphoma (Nishikori et al, 2003). Consistent with an oncogenic function, BCL3 can directly transform cells and induce tumor growth in vivo (Viatour et al, 2004).…”
Section: Introductionmentioning
confidence: 74%
“…High BCL3 expression has also been reported in a subgroup of anaplastic large-cell lymphoma (Nishikori et al, 2003). Consistent with an oncogenic function, BCL3 can directly transform cells and induce tumor growth in vivo (Viatour et al, 2004).…”
Section: Introductionmentioning
confidence: 74%
“…19 In anaplastic large-cell lymphoma, a prior study has shown that BCL-3 expression and both genetic and epigenetic modifications of the bcl-3 gene may be associated with oncogenesis. 13 Izban and colleagues 30 have reported that NF-kB p65 is expressed in cutaneous T-cell lymphoma cell lines and neoplastic T lymphocytes from patient samples of mycosis fungoides, and they also showed that nuclear NF-kB activity is required for cell survival and resistance to apoptosis in the neoplastic cells. Although BCL-3 has a strong preference towards p50 and p52 It is also known that stimuli such as tumor necrosis factor a, interleukin1b not only cause nuclear accumulation of p50-p65 heterodimers, but also induce formation of BCL-3-p50 complexes.…”
Section: Bcl-3 In Lymphomasmentioning
confidence: 99%
“…For example, two recent studies have shown high levels of BCL-3 expression in ALKpositive anaplastic large-cell lymphoma. 13,14 However, presence or absence of BCL-3 expression is unknown for most of the wide variety of lymphoma types defined in the recently published World Health Organization (WHO) classification. 15 In this study, we used an immunohistochemical method and a commercially available monoclonal antibody specific for BCL-3 to assess for expression in 353 cases of non-Hodgkin lymphoma and Hodgkin lymphoma.…”
mentioning
confidence: 99%
“…30 Bcl-3 protein levels are high in such leukemias, as well as in some lymphomas, including a subgroup of anaplastic large lymphoma (ACLC) with t(2;5)(q23;q35), where a combination of genetic and epigenetic modifications is supposed to lead to bcl-3 overexpression. [31][32] Bcl-3 protein shares with IkB family proteins the presence of ankyrin domains; however, at variance with the other IkB proteins, it is mainly nucleoplasmic and can enhance NFkB-dependent transcription (33)(34)(35). Indeed, in the cell nucleus, Bcl-3 can either interact with suppressor p50 homodimers and remove them from DNA, or bind to p52 homodimers to coactivate transcription.…”
mentioning
confidence: 99%